The Influence of Gastronomic Tourism on Tourist Satisfaction in Gianyar Regency - Gayatri; Ni Luh Sari Widhiyani (E-Jurnal Akuntansi, 2025)
This research attempts to examine the effects of gastronomic perceived value, gastronomic image, and gastronomic experience on both gastronomic satisfaction and visitor loyalty in Gianyar Regency, as well as to investigate the influence of gastronomic satisfaction on visitor loyalty. A casual quantitative research design was employed, with data collected via survey questionnaires. The results reveal that both gastronomic perceived value and gastronomic experience positively affect gastronomic satisfaction and visitor loyalty. While gastronomic satisfaction significantly boosts visitor loyalty, gastronomic image—despite enhancing satisfaction—does not directly impact visitor loyalty.